The Development of Smart House Model in Garut; The Advancement of Non-Formal Education Program - Sudaryana, Bambang (Asian Journal of Contemporary Education, 2018)
Smart House is a means to involve citizens in inclusive education; an additional education outside of school. In Smart House, especially school-aged children can explore their own potential as well as motivate themselves to achieve a higher intelligence level. In Smart House, there are five centers of education, including the library space with 6000 copies of books collection, and centers of educational facilities. The objective of this study is to identify communication strategies, the role of Smart House as non-formal education, and to know the factor supporting and inhibiting it. The method used is a descriptive quantitative method to describe data objectively; data collection is conducted through observation, interview, and documentation. The number of respondents in this study was 50. Based on this study, it was found that many people do not take advantage of Smart House due to factors come from Smart House, and factors come from the community. The study concludes that the role of Smart House affects the access of services of non-formal education programs, as well as the function, the purpose, and the benefits of Smart House as a place of learning from children to the elderly with activities that meet the needs of the poor people. The impact of Smart House is the increasing power of intellectual for rural children at the age of learning and as an accommodation of creativity for the population, and it is helpful to increase family income.